Effects of horizontal tube arrays on heat transfer in an external heat exchanger. (25th November 2020) - Cai, Runxia; Deng, Boyu; Tao, Xin; Zhang, Yi; Yang, Hairui; Yue, Guangxi; Zhang, Man
Highlights: Local heat transfer coefficients with horizontal tube arrays were measured. Effects of different arrangements of tube arrays were compared. The packet renewal model was used to explain the non-uniform phenomenon. Applicability of different heat transfer models were analyzed. Abstract: Few studies have addressed the impact of horizontal tube arrays on the local bed-to-wall heat transfer coefficients. Therefore, in this paper, the local heat transfer coefficients were measured in an external heat exchanger with inline and staggered horizontal tube arrays. The corresponding gas–solid hydrodynamics on the tube surface was obtained by using the optical fiber probe. The lateral distribution of the heat transfer coefficients was found to be non-uniform, and the maximum values were achieved at the position of 0.64 times half-width. The impact of the tube arrays on the heat transfer coefficients varied with the lateral locations and the configuration of tube arrays. Compared with cases without tube arrays, the inline tube array reduced the heat transfer coefficients in the bed center but increased those near the column wall. Compared with the inline tube array, the staggered array increased the deviations of heat transfer coefficients both in the bed center and in the wall region. The modified packet renewal model could reflect the trend in the variation of the heat transfer coefficients along the bed width but slightly overestimated the values. The overall average heat transfer coefficients were also compared to the results predicted using common published correlations.